Nuevo hospital local de Candelaria Valle del Cauca. (2023)
The present investigation tries to investigate what are the needs and problems in health for the potentialization of the hospital infrastructure in the municipality of Candelaria from the development V alle del Cauca of a projective strategy of Sustainable Urban Architectural design.